2020
DOI: 10.21203/rs.3.rs-28100/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of mouth breathing on facial skeletal development and malocclusion in children: A systematic review and meta-analysis.

Abstract: BACKGROUND: Mouth breathing is closely related to the facial skeletal development and malocclusion. The purpose of this systematic review and meta-analysis was to assess the effect of mouth breathing on facial skeletal development and malocclusion in children. METHODS: An electronic search in PubMed, the Cochrane Library, Medline, Web of Science, EMBASE and Sigle through February 23rd, 2020, was conducted. Methodological quality assessments of the selected articles were performed using the Newcastle-Ottawa Sca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A total of seven studies were included. The results of this review revealed that mouth breathing can be associated with an underdevelopment of the mandible, where it rotates backward and downward, and a steep occlusal plane [16]. Notably, there was little effect on the maxilla and a tendency of lip inclination in mouth breathing children.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 85%
See 4 more Smart Citations
“…A total of seven studies were included. The results of this review revealed that mouth breathing can be associated with an underdevelopment of the mandible, where it rotates backward and downward, and a steep occlusal plane [16]. Notably, there was little effect on the maxilla and a tendency of lip inclination in mouth breathing children.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 85%
“…Notably, there was little effect on the maxilla and a tendency of lip inclination in mouth breathing children. This, to date, is the first systematic review and meta-analysis that assessed this relationship [16]. It is an interesting finding which can draw conclusions on the severity of the malocclusion, but it cannot give an indication of whether the prevalence of malocclusion is indeed increased due to the mouth breathing.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 91%
See 3 more Smart Citations